Uncertainties Associated With Simulating Regional Sea Surface Height and Tides: A Case Study of the East China Seas - Jiang, Long; Lu, Xinyu; Xu, Wenlong; Yao, Peng; Cheng, Xuhua (Frontiers in Marine Science, 2022)
Modeling sea surface height (SSH) and tides is important but challenging in shelf seas. The Eastern China Seas (ECSs) is such a shelf sea with large inter-model deviations in prior studies. In order to assess and compare the possible uncertainty sources, numerical scenarios of varying the open boundary forcing, bottom roughness length scale, atmospheric forcing, grid resolution, and regional bathymetry were conducted in a hydrodynamic model of the ECSs. Results indicate that bathymetry data and open boundary forcing with inadequate accuracy generate uncertainties in SSH and tides locally and throughout the basin. An increase in bottom roughness enhances tidal dissipation and shifts amphidromes to the left relative to the incoming Kelvin waves, causing SSH variations in the ECSs. Refining the model resolution from 4 km to 2 km mainly affects nearshore SSH and tides due to minor changes in depicted coastlines. Using different reanalysis meteorological data appears more important on the episodic than annual scale. It is highlighted that some uncertainty sources have opposing effects on SSH or tides and counteract their individual biases, making it difficult to achieve a realistic simulation. For example, increasing bottom roughness can not only compensate effects of overestimated tidal amplitude at open boundaries, but also balance out the overestimated M2 phase along the West Coast of Korea in a coarser-resolution model. Based on findings in this study, suggestions are provided for further reducing uncertainties in SSH and tide modeling in the ECSs and other shelf seas.